2018
DOI: 10.1098/rsos.180617
|View full text |Cite
|
Sign up to set email alerts
|

Soluble hexamethyl-substituted subphthalocyanine as a dopant-free hole transport material for planar perovskite solar cells

Abstract: Boron subphthalocyanine (SubPc) has special physical and chemical properties, originating from its non-centrosymmetric, near-planar taper structure and large conjugated system; it can act as an alternative to the small molecule hole-transporting material 2,2′,7,7′-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9′-spirobifluorene in perovskite solar cells (PSCs). To achieve a higher solubility in common organic solvents and a more suitable highest occupied molecular orbital energy level that aligns with the valence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…chlorobenzene, 13 o -dichlorobenzene, 14,15 or 1-chloronaphthalene 16 ). 11 SubPcs synthesis has also been carried out by addition of a 1 M solution of BCl 3 in heptanes 17–19 or dichloromethane 20–27 to a solution of the starting phthalonitrile in a high-boiling solvent such as p -xylene, 22,24 1-chloronaphthalene, 18 o -dichlorobenzene, 17,19,21,23,25,26 1,2,4-trichlorobenzene 20 or dimethyl sulfoxide. 11,27 Microwave irradiation has also been employed for SubPc preparation.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…chlorobenzene, 13 o -dichlorobenzene, 14,15 or 1-chloronaphthalene 16 ). 11 SubPcs synthesis has also been carried out by addition of a 1 M solution of BCl 3 in heptanes 17–19 or dichloromethane 20–27 to a solution of the starting phthalonitrile in a high-boiling solvent such as p -xylene, 22,24 1-chloronaphthalene, 18 o -dichlorobenzene, 17,19,21,23,25,26 1,2,4-trichlorobenzene 20 or dimethyl sulfoxide. 11,27 Microwave irradiation has also been employed for SubPc preparation.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…Further research on this SubPc-based HTMs was reported by Wan et al describing the use of a new Me 6 SubPc-Cl. 26 In this case the SubPc was deposited by spin coating and integrated in the following solar cell configuration: FTO/SnO 2 /PCBM/perovskite/Me 6 SubPc-Cl/Au. The layer morphology was again evaluated by SEM measurements and revealed that the SubPc formed a smooth and flat surface in contact with perovskite and Au layers.…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…In the past few years, several efforts have been made to design new efficient, low cost, and easy processable HTMs involving porphyrinoids (e.g., porphyrins, [41][42][43][44] phthalocyanines, [45][46][47][48][49][50] and subphthalocyanines [51,52] ) thanks to their outstanding chemical, thermal, and photostability, along with an efficient light-harvesting ability throughout a large portion of the solar emission spectrum. Within the family of porphyrinoids, corroles have gained increasing attention, being extensively employed as dyes for solar energy conversion and in optoelectrical devices.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, organic SubPcs have successfully been applied in the field of photovoltaics as light harvesters due to their excellent optical and semiconducting properties [21][22][23][24] . Recently, SubPcs have also been used as hole transport materials (HTM) for organometallic halide perovskite solar cells because of its stability and long excitation diffusion length 16,25 showing its potential as alternative to the most commonly used spiro-OMeTAD 26,27 . A protective effect of the SubPc over the perovskite from degradation has also been reported 16 , or as passivating agent of the defects within the perovskite film.…”
Section: Introductionmentioning
confidence: 99%